'Egypt': legitimation at the museum. (15th September 2016) - James, N.
Abstract : Heracleion and Canopus were towns recorded in Classical sources about the Nile delta. Surveys near Alexandria in 1996 found ruins poking through the sands under four or five fathoms of murky water. Revealing complexes of temples, excavation then confirmed that these were the remains of Heracleion and the eastern part of Canopus, dating from the Late Dynastic era. The discoveries show how Greek traders had settled, and how the towns then thrived, after Alexander the Great's conquest (332 BC), during the Hellenistic or Ptolemaic period. Following a somewhat smaller display in Paris in 2015–2016, many of the finds can now be admired at the British Museum until 27 November 2016 in the exhibition 'Sunken cities: Egypt's lost worlds'.